1993
DOI: 10.1159/000216905
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prophylaxis of Deep Venous Thrombosis in Outpatients with Injury of the Lower Limb

Abstract: 253 outpatients were included in a prospective randomized study. All patients had incidences of injuries of the lower limb immobilized by a plaster cast. 126 patients (group I) received a subcutaneous injection of Fraxiparin daily, and 127 patients (group II) received no thromboprophylaxis. Without prophylaxis 21 (16.5%) cases developed a thrombosis, and with prophylaxis a thrombosis could be proven in 6 (4.8%) patients only (p < 0.01). Thus, for all patients with an injury of the lower limb being immobilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
122
0
4

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(135 citation statements)
references
References 5 publications
(7 reference statements)
9
122
0
4
Order By: Relevance
“…Comparison with others is, however, difficult since previous randomized studies (Kujath et al 1993, Kock et al 1995, Jorgensen et al 2002, Lassen et al 2002 have included a heterogeneous mix of patients with different lower limb injuries, treated with or without surgery, factors that may influence the effect of the thromboprophylaxis given and the risk of DVT (Geerts et al 2004). Only 1 of the previous studies (Lassen et al 2002) was placebo-controlled and phlebography was mandatory in only 2 of these studies (Jorgensen et al 2002, Lassen et al 2002.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison with others is, however, difficult since previous randomized studies (Kujath et al 1993, Kock et al 1995, Jorgensen et al 2002, Lassen et al 2002 have included a heterogeneous mix of patients with different lower limb injuries, treated with or without surgery, factors that may influence the effect of the thromboprophylaxis given and the risk of DVT (Geerts et al 2004). Only 1 of the previous studies (Lassen et al 2002) was placebo-controlled and phlebography was mandatory in only 2 of these studies (Jorgensen et al 2002, Lassen et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Only 1 of the previous studies (Lassen et al 2002) was placebo-controlled and phlebography was mandatory in only 2 of these studies (Jorgensen et al 2002, Lassen et al 2002. Kujath et al (1993) and Kock et al (1995) used unblinded treatment, and ultrasound to screen for DVT. This method was poorly validated for DVT screening at that time (Wells et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients immobilized with plaster casts due to lower leg injuries, Kujath et al demonstrated a reduction in the incidence of DVT when prophylactic treatment was used [9]. On the other hand, Patel et al believe that routine use of anticoagulation might be unwarranted (Table 2) [3].…”
Section: Discussionmentioning
confidence: 99%
“…Kujath, et al, studied DVT in 253 outpatients with lower limb injuries who were immobilized in a plaster cast. 24 This was a prospective randomized study, and half received Fraxiparin injected subcutaneously daily until the cast was removed, and the other half received no thromboprophylaxis. DVT occurred in 16.5% of patients not given VTE prophylaxis compared to only 4.8% in the Fraxiparin group.…”
Section: Immobilization and Venous Thromboembolismmentioning
confidence: 99%